2022
DOI: 10.3390/fishes7010023
|View full text |Cite
|
Sign up to set email alerts
|

Otolith Microchemistry and Demographic History Provide New Insight into the Migratory Behavior and Heterogeneous Genetic Divergence of Coilia grayii in the Pearl River

Abstract: Coilia grayii is the anadromous form of anchovy that is distributed in the East and South China Seas. It is a common fish species in the estuarine area of the Pearl River. Nevertheless, freshwater populations appear upstream in the Pearl River, but the migratory pathway has been mostly impeded by dam construction. Behavioral differences and constrained habitat within tributaries are suspected of promoting genetic divergence in these populations. In this study, we investigated the migratory behavior and genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
0
0
Order By: Relevance
“…The Pearl River, which is the third largest river in the drainage basin area in mainland China, is composed of three main tributaries, namely, the Bei River, Dong River, and Xi River. Previous studies have shown that some species do not have obvious geographic population structure in the Pearl River drainage, such as Anguilla japonica (Zhong et al, 2022), Coilia grayii (Wang et al, 2022a), M. terminalis (Chen et al, 2020), and Hemibagrus guttatus (Yang and He, 2008). However, others had patterns concordant with predicted phylogeographic structure: the Dong and Xi/Bei Rivers contained two phylogeographic groups of S. scherzeri (Lin et al, 2022), and the Xi and Dong/Bei Rivers harbored two phylogeographic groups of G. fokiensis fokiensis (Chen et al, 2007).…”
Section: Phylogeography Of Barbodes Semifasciolatusmentioning
confidence: 99%
“…The Pearl River, which is the third largest river in the drainage basin area in mainland China, is composed of three main tributaries, namely, the Bei River, Dong River, and Xi River. Previous studies have shown that some species do not have obvious geographic population structure in the Pearl River drainage, such as Anguilla japonica (Zhong et al, 2022), Coilia grayii (Wang et al, 2022a), M. terminalis (Chen et al, 2020), and Hemibagrus guttatus (Yang and He, 2008). However, others had patterns concordant with predicted phylogeographic structure: the Dong and Xi/Bei Rivers contained two phylogeographic groups of S. scherzeri (Lin et al, 2022), and the Xi and Dong/Bei Rivers harbored two phylogeographic groups of G. fokiensis fokiensis (Chen et al, 2007).…”
Section: Phylogeography Of Barbodes Semifasciolatusmentioning
confidence: 99%